Process-Service Interactions Using a SOA-BPM-Based Methodology - Patricia, B.; Perez, G.; Giandini, R.; Diaz, J. (2011 30th International Conference of the Chilean Computer Science Society, 2011)
Reducing the gap between the definition, modeling and management of business definition, modeling and management of business processes and the realization of the main processes functions through software services requires a methodological approach. Addressing such gap, this paper focuses on the interactions between the activities of a business process and the functionality provided by software services. It presents a meta-model to formally specify such interactions. The proposed meta-model is instantiated through a case study. Lessons learnt through the development of an example were used to define a graphic editor prototype, as an automated tool for managing interactions between business processes and software services. The proposed approach enables the alternative application of top-down and bottom-up analysis techniques for modeling processes and services, and assists developers with an integrated tool for modeling business processes and software services in a seamlessly combined way.